Glaucoma and increased central corneal thickness in aphakic and pseudophakic patients after congenital cataract surgery. Issue 9 (17th May 2006) - Simsek, T; Mutluay, A H; Elgin, U; Gursel, R; Batman, A
Abstract : Aim: To compare the mean central corneal thickness (CCT) among aphakic and pseudophakic patients following congenital cataract surgery with age matched controls. Methods: This study included 43 eyes of 43 aphakic and pseudophakic patients following congenital cataract surgery. 44 healthy, age and sex matched volunteers were recruited for comparison with the patients. After a complete eye examination, corneal thickness and intraocular pressure were measured. Results: In the study group, 33 eyes were aphakic, and the remaining 10 eyes were pseudophakic. The median CCT was 556.0 μm (range 490–640 μm) in the control group and 626 μm (range 523–870 μm) in the study group (p<0.05). There was a significant difference in CCT between aphakic and pseudophakic eyes in which an intraocular lens (IOL) had been implanted at the time of congenital cataract surgery (p = 0.011). The same difference was not observed between aphakic and pseudophakic eyes in which an IOL had been implanted secondarily (p = 0.835). The median age of the patients at the time of lensectomy was 24 months (range 1 week to 120 months). There was a negative correlation between the age at lensectomy and CCT ( r = −0.485, p = 0.001). Conclusion: Aphakic and pseudophakic patients have significantly thicker corneas than age matched controls. This difference can have an important effect on interpreting intraocular pressures in these patients. It is also important to assess the effects of early surgery for congenital cataracts, as well as those of primary and secondary IOL implantation, on CCT.